2016
DOI: 10.17795/ajcmi-36521
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of A2143G and A2144G Point Mutations Responsible for Clarithromycin Resistance among Helicobacter pylori Strains in Bushehr, Iran

Abstract: Background: Resistance to clarithromycin in Helicobacter pylori has become one of the most important reasons for failure of antibiotic eradication therapies. This resistance is predominantly caused by point mutations in the peptidyl transferase region of 23S rRNA. Objectives: The aim of this study was to determine the prevalence of the A2143G, A2144G, and A2143C point mutations among H. pylori strains from gastric biopsy specimens in Bushehr, in the southwest of Iran. Patients and Methods: Gastric biopsy speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In this study, although the relative frequency of clarithromycin resistance was higher in females than males, the difference was not significant. This is consistent with the findings of others [12,32]. The consumption of new macrolides, which are commonly prescribed in the elderly, can lead to more mutations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, although the relative frequency of clarithromycin resistance was higher in females than males, the difference was not significant. This is consistent with the findings of others [12,32]. The consumption of new macrolides, which are commonly prescribed in the elderly, can lead to more mutations.…”
Section: Discussionsupporting
confidence: 92%
“…To deparaffinize the tissue sections, the slides were subsequently immersed in hexane and absolute ethanol (Merck, Germany) twice, each time for 30 minutes. After air-drying of the slides, they were then ready for checking by FISH [12].…”
Section: Preparation Of Gastric Biopsy Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the frequency in the sampled population in this study, is in line with the frequencies reported in other regions, 0.01 (1/73)[ 21 ] and 0.81(9/11)[ 20 - 23 ]. This mutation was first reported in H. pylori isolates resistant to clarithromycin in Colombia, which indicates that it may be associated with the inclusion of strains from high frequency countries such as South Korea (frequency of 0.57)[ 15 ]; Japan (frequency of 0.7)[ 24 ] and Turkey (frequency between 0.29 and 0.81[ 20 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mutations associated with clarithromycin resistance in the H. pylori isolates described in this study (A2144G, C2196T, and T2183C), are located in 23S rRNA gene V domain, as reported in the current literature[ 3 ]. Inhibition of the action of the macrolide may be due to spatial alterations in the V domain of 23S rRNA gene, which inhibit the target, as seen in transversion mutations A2143G, A2142G, A2142C[ 3 ], A2144G[ 18 , 19 , 22 ], where a nitrogenous base with two H groups (Adenine) is changed for another with three H groups (Guanine and Cytosine), with the inherent spatial alteration of the molecular structure, a phenomenon similar in transitions C2196T and T2183C[ 17 ].…”
Section: Discussionmentioning
confidence: 99%